2019
DOI: 10.1016/j.isci.2019.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium perfringens Epsilon Toxin Compromises the Blood-Brain Barrier in a Humanized Zebrafish Model

Abstract: Summary Clostridium perfringens epsilon toxin (ETX) is hypothesized to mediate blood-brain barrier (BBB) permeability by binding to the myelin and lymphocyte protein (MAL) on the luminal surface of endothelial cells (ECs). However, the kinetics of this interaction and a general understanding of ETX's behavior in a live organism have yet to be appreciated. Here we investigate ETX binding and BBB breakdown in living Danio rerio (zebrafish). Wild-type zebrafish ECs d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 86 publications
(132 reference statements)
1
12
0
Order By: Relevance
“…ETX does not bind to wild-type zebrafish endothelial cells and, consequently, the toxin has no effect. However, a humanized zebrafish model expressing human MAL in endothelial cells binds to ETX and responds by producing blood–brain barrier leakage, blood vessel stenosis, perivascular edema and blood stasis [ 157 ]. In mice, MAL expression was found in the endothelium of some lung vessels, supporting the hypothesis that MAL is a key element in the ETX-induced perivascular edema in the lungs [ 158 ].…”
Section: Mal and The Clostridial Epsilon Toxinmentioning
confidence: 99%
“…ETX does not bind to wild-type zebrafish endothelial cells and, consequently, the toxin has no effect. However, a humanized zebrafish model expressing human MAL in endothelial cells binds to ETX and responds by producing blood–brain barrier leakage, blood vessel stenosis, perivascular edema and blood stasis [ 157 ]. In mice, MAL expression was found in the endothelium of some lung vessels, supporting the hypothesis that MAL is a key element in the ETX-induced perivascular edema in the lungs [ 158 ].…”
Section: Mal and The Clostridial Epsilon Toxinmentioning
confidence: 99%
“…However, there is no absolute relationship between molecular weight and BBB penetration [ 36 ]. A recent study revealed that the epsilon toxin (ETX) can cross the BBB by binding to the lymphocyte protein (MAL) on the luminal surface of endothelial cells [ 37 ]. Thus, macromolecules with high molecular weights are also likely to cross the BBB in a unique way.…”
Section: Discussionmentioning
confidence: 99%
“…Several microbes may cause disruption of the integrity of the BBB. Specifically, the bacteria Clostridium perfinges produces Epsilon toxin, which increases BBB permeability in zebrafish [212]. Other bacteria such as Mycobacterium tuberculosis and Mycobacterium marinum can cross the BBB and reach the brain to cause infection [213].…”
Section: Microbial Infectionmentioning
confidence: 99%